Persuasive Strategies Used by Joe Biden and Kamala Harris in Their Campaign Speeches - Vinia Welliani Arella (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This study aims to analyze the persuasive strategies employed by Joe Biden and Kamala Harris in their campaign speeches, guided by the theoretical framework proposed by Beebe and Beebe (2012). Through qualitative analysis of paragraphs extracted from two campaign speech transcripts, the study identifies the distinct persuasive strategies of each speaker. Joe Biden used causal reasoning, specific evidence, evidence to tell a story, concrete examples, emotion-arousing words, metaphors and similes, fear appeals, appeal to emotions of hope, appeal to emotions of courage, and shared myths, while Kamala Harris used deductive reasoning, specific evidence, evidence to tell a story, concrete examples, emotion-arousing words, fear appeals, appeal to emotions of hope, and appeal to emotions of courage.